Evaluation of antimycobacterial rhamnolipid production from non-cytotoxic strains of Pseudomonas aeruginosa isolated from rhizospheric soil of medicinal plants - Mishra, Alok K; Dubey, Rikesh K; Yabaji, Shivraj M; Jaiswal, Swati (International Journal of Biological Research, 2016)
RhamnolipidsÂ (RLs) are the bacterial derived biosurfactantsÂ and known for a wide range of industrial and therapeutic applications. They exhibit potent anti-bacterial activity against various gram positive, gram negative and acid fast bacteria including Mycobacterium tuberculosis. Since, PseudomonasÂ is one of the largest known genuses containing a variety ofÂ rhamnolipid producing strains. Therefore, in thisÂ study, weÂ selectively isolated the PseudomonasÂ aeruginosa strains fromÂ the rhizospheric soilÂ of the Indian plants of medicinalÂ value, e.g.Â Azadirachta Indica and Ficus spp., and evaluated them for their natural ability to produce antibacterialÂ rhamnolipids. The bacteria were identified on the basis of 16s rRNA sequencing and biochemical characterization. Among 33 of P. aeruginosa isolates from different soil samples, four isolates showed potent inhibitory activity against methicillin resistant Staphylococcus aureus (MRSA) and fast growerÂ mycobacterialÂ spp. The inhibitory potential of the isolates was found to be correlated with their ability to produce RLs inÂ the medium. The industrial viability of the strains was assessed on the basis ofÂ cytotoxicity determining alternative allele,Â exoS/exoUÂ and cell mediated cytotoxicity against murine macrophages J774.1. The newly isolated strains harborÂ exoSÂ allele and exhibits lower cell mediated cytotoxicity on macrophage cell line as compared to the clinical strains PA-BAA-427 and PA-27853 used asÂ a controlÂ in this study. Evaluation of antimycobacterial rhamnolipid production from non-cytotoxic strains of Pseudomonas aeruginosa isolated from rhizospheric soil of medicinal plants